Optimalisasi Olahan Jamu sebagai Upaya Pemberdayaan Masyarakat di Perum Graha Mitra Asri RT.11/RW.01 Kelurahan Sambikerep, Kecamatan Sambikerep Surabaya - Anggreini, Riski Ayu; Rahmadhini, Noni; Kamandang, Zetta Rasulia (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The Covid-19 pandemic over the past year has made the Indonesian government make several policies, such as several activities, to increase the increase in positive cases, including social distancing and PSBB (Large-Scale Social Restrictions). One of the impacts of these policies is an increase in the number of jobs produced by many job providers who reduce the number of employees. In this activity, we choosed herbal products, because they are abundant, easy to access, and low in price, thus it could be used as business opportunities. The herbal product is then optimized in a way that is developed into other products such as herbal latte and herbal boba, this is done so that the market segmentation for herbal products is wider and can be used as an idea for entrepreneurship. In addition, it can also educate the health benefits of herbal medicine. This community service partner is a resident of Perum Graha Mitra Asri RT.11/RW.01, Sambikerep Village, Sambikerep District, Surabaya. The activity method used is starting from coordination and preparation with potential partners, counseling, and manufacturing products training.